O izvoru poezije - Kos, Dejan (Primerjalna književnost, 2018)
Throughout the history of European thought there have been two types of discussions about the origins of poetry: those that do not capitalize the initial letter of the term "origin" and those that do. The former discussions are those that in recent centuries have adopted the language of many subtypes of scientific discourse (ranging from natural sciences, social sciences and cognitive science to semiotics, humanistic disciplines and cultural history), while the transgressive logic of the latter has adopted certain theistic concepts. The two varieties of thought are often connected with one another, and the present paper searches for their complementarity. When the causative logic of science is no longer merely a way to observe the subject area, but itself becomes the subject of observation, transgression becomes part of its own starting-points. The logical and ontological impasses of scientific assumptions reveal the same trans-rationality that is presumed in theistic discourses. The processes of self-referentiality are also followed by poetry, which by means of "de-causalisation" and "de-ontologisation" sharpens the awareness about producing the socially accepted versions of reality. The more efficient the poetic processes are, the deeper this awareness sinks into the layers that produced it. When in the poetic equilibriums even existence and non-existence are equalized, something greater than both is revealed in the radical arbitrariness. The final, non-arbitrary depths of poetry speak in the blind spot of the causal and ontological world.
Keywords: poetry; poezija; epistemologija; epistemology; causality; vzročnost; ontologija; ontology; duhovnost; spirituality